preliminary study of the effect of probiotic Streptococcus salivarius K12 on oral malodour parameters - Burton, J.P; Chilcott, C.N; Moore, C.J; Speiser, G; Tagg, J.R (Journal of applied microbiology, 2006)
To determine whether dosing with bacteriocin-producing Streptococcus salivarius following an antimicrobial mouthwash effects a change in oral malodour parameters and in the composition of the oral microbiota of subjects with halitosis. Twenty-three subjects with halitosis undertook a 3-day regimen of chlorhexidine (CHX) mouth rinsing, followed at intervals by the use of lozenges containing either S. salivarius K12 or placebo. Assessment of the subjects' volatile sulphur compound (VSC) levels 1 week after treatment initiation showed that 85% of the K12-treated group and 30% of the placebo group had substantial (>100 ppb) reductions. The bacterial composition of the saliva was monitored by culture and PCR-denaturing gradient gel electrophoresis (PCR-DGGE). Changes in the PCR-DGGE profiles occurred in most subjects following K12 treatment. In vitro testing showed that S. salivarius K12 suppressed the growth of black-pigmented bacteria in saliva samples and also in various reference strains of bacteria implicated in halitosis. Administration of bacteriocin-producing S. salivarius after an oral antimicrobial mouthwash reduces oral VSC levels. The outcome of this preliminary study indicates that the replacement of bacteria implicated in halitosis by colonization with competitive bacteria such as S. salivarius K12 may provide an effective strategy to reduce the severity of halitosis.